Re-evaluation of Pleistocene and Holocene long bone robusticity trends with regards to age-at-death estimates and size standardization procedures - Friedl, Lukáš; Eisová, Stanislava; Holliday, Trenton W (Journal of Human Evolution, 2016)
Long-term trends in robusticity of lower limb bones in the genus Homo through the Pleistocene until the present have been proposed, which have been interpreted as a consequence of decreasing levels of mobility and activity patterns, changes in lifestyle, and environmental factors. There has also long been evidence that skeletal strength increases over an individual's lifespan. This increase is caused by continuous bone remodeling that optimizes the structure of a bone to resist mechanical loadings and creates a balance between endosteal resorption and subperiosteal apposition. However, none of the previous studies of temporal trends in robusticity has considered both processes and analyzed how individual age-related robusticity might influence higher-level temporal trends. This paper therefore explores temporal trends in robusticity of lower limb long bones within the genus Homo and considers how individual ages-at-death can confound published evolutionary trends, given the fact that some aspects of relative bone strength tend to increase over individual lifespans. Cross-sectional diaphyseal properties of the midshaft and proximal femur and midshaft tibia of Pleistocene and early Holocene individuals, together with data on age-at-death are used to analyze changes in relative bone strength relative to individuals' ages and evolutionary time. The results show increasing bone strength in adulthood until the fourth decade and then a slight decrease, an observation that conforms to previously published results on recent human populations. However, no significant impact of age-at-death on the trends along an evolutionary trajectory has been detected. The evolutionary trends in femoral and tibial relative strength can be described as fluctuating, probably as a consequence of changing mobility patterns, environmentally and technologically influenced behaviors, and demographic processes. The differences between evolutionary trends published in several studies are explained primarily as a result of different ways of standardizing cross-sectional parameters for size, and differences in sample composition.
Keywords: biomechanika; Femur; lidé; mladiství; Adult; Middle Aged; Female; věkové faktory; biologická evoluce; Adolescent; Humans; kostní denzita; Tibia; lidé středního věku; mužské pohlaví; mladý dospělý; zvířata; Bone Density; Biomechanical Phenomena; ženské pohlaví; Young Adult; Age Factors; Animals; Biological Evolution; Male; dospělí; tibie; Hominidae; femur